Analisis Rendahnya Kemampuan Membaca Pemahaman Siswa Sekolah Dasar dalam Mata Pelajaran Bahasa Indonesia (Jurnal Motivasi Pendidikan dan Bahasa, 2025)
This study aims to analyze the factors that cause the low reading comprehension ability of elementary school students in Indonesian subjects. The method used is library research by analyzing various literature from 2019-2024. The results of the study show that the reading comprehension ability of elementary school students is still relatively low with various causative factors including internal and external factors. Internal factors include students' reading interests, motivation, and cognitive abilities. External factors include learning methods, infrastructure, and environmental support. This study recommends the need to innovate learning methods and improve supporting facilities to improve students' reading comprehension skills.